Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(x-3\right)^2-4=0\)
\(\left(x-3\right)^2=0+4\)
\(\left(x-3\right)^2=4\)
\(\left(x-3\right)^2=\pm4\)
\(\left(x-3\right)^2=\pm2^2\)
\(\orbr{\begin{cases}x-3=2\\x-3=-2\end{cases}}\)
\(\orbr{\begin{cases}x=5\\x=1\end{cases}}\)
b) \(\left(2x+3\right)^2-\left(2x+1\right)\left(2x-1\right)=22\)
\(4x^2+12x+9-4x^2+1=22\)
\(12x+10=22\)
\(12x=22-10\)
\(12x=12\)
\(x=1\)
c) \(\left(4x+3\right)\left(4x-3\right)-\left(4x-5\right)^2=16\)
\(16x^2-9-16x^2+40x-25=16\)
\(-34+40x=16\)
\(40x=16+34\)
\(40x=50\)
\(x=\frac{50}{40}=\frac{5}{4}\)
d) \(x^3-9x^2+27x-27=-8\)
\(x^3-9x^2+27x-27+8=0\)
\(x^3-9x^2+27x-19=0\)
\(\left(x^2-8x+19\right)\left(x-1\right)=0\)
Vì \(\left(x^2-8x+19\right)>0\) nên:
\(x-1=0\)
\(x=1\)
e) \(\left(x+1\right)^3-x^2\left(x+3\right)=2\)
\(x^3+2x^2+x+x^2+2x+1-x^2-3x^2=2\)
\(3x+1=2\)
\(3x=2-1\)
\(3x=1\)
\(x=\frac{1}{3}\)
a) (x - 1)3 - x(x - 2)2 - (x - 2) = 0
<=> x3 - 2x2 + x - x2 + 2x - 1 - x3 + 4x2 - 4x - x + 2 = 0
<=> x2 - 2x + 1 = 0
<=> x2 - 2.x.1 + 12 = 0
<=> (x - 1)2 = 0
x - 1 = 0
x = 0 + 1
x = 1
=> x = 1
a)Ta có : \(\left(x-1\right)^3-x\left(x-2\right)^2-\left(x-2\right)=0\)
\(=>\left(x-1\right)^3-\left(x^2-2x\right)\left(x-2\right)-\left(x-2\right)=0\)
\(=>\left(x-1\right)^3-\left(x-2\right)\left(x^2-2x+1\right)=0\)
\(=>\left(x-1\right)^3-\left(x-2\right)\left(x-1\right)^2=0\)
\(=>\left(x-1\right)^2\left(x-1-x+2\right)=0\)
\(=>\left(x-1\right)^2=0=>x-1=0=>x=1\)
Vậy x=1
b)(2x+5)(2x-7)-(4x+3)2=16
\(=>4x^2-4x-35-16x^2-24x-9-16=0\)
\(=>-\left(12x^2+28x+60\right)=0\)
\(=>12\left(x^2+\frac{7}{3}x+\frac{5}{3}\right)=0\)
\(=>x^2+\frac{7}{3}x+\frac{49}{36}+\frac{11}{36}=0=>\left(x+\frac{7}{6}\right)^2+\frac{11}{36}=0\)
Lại có \(\left(x+\frac{7}{6}\right)^2\ge0=>\left(x+\frac{7}{6}\right)^2+\frac{11}{36}\ge\frac{11}{36}>0\)
Vậy ko có giá trị nào của x thỏa mãn đề bài
\(=>x^2+\frac{7}{3}x+\frac{49}{36}+\frac{11}{36}=0=>\left(x+\frac{7}{6}\right)^2+\frac{11}{36}=0\)
a) \(\dfrac{16+x}{x^2-2x}+\dfrac{18}{2x-x^2}\)
\(=\dfrac{16+x}{x^2-2x}-\dfrac{18}{x^2-2x}\)
\(=\dfrac{16+x-18}{x^2-2x}\)
\(=\dfrac{x-2}{x\left(x-2\right)}\)
\(=\dfrac{1}{x}\)
a, \(5\left(2x+1\right)-2x-1=16\)
\(\Leftrightarrow10x+5-2x-1-16=0\Leftrightarrow8x-12=0\Leftrightarrow x=\frac{3}{2}\)
b, \(4x\left(x+5\right)=3\left(x+5\right)\Leftrightarrow4x\left(x+5\right)-3\left(x+5\right)=0\)
\(\Leftrightarrow\left(4x-3\right)\left(x+5\right)=0\Leftrightarrow x=\frac{3}{4};-5\)
c, \(x\left(x-2\right)=3-6\Leftrightarrow x^2-2x+3=0\)
vô nghiệm
a, \(4\left(18-5x\right)-12\left(3x-7\right)=15\left(2x-16\right)-6\left(x+14\right)\)
\(\Leftrightarrow72-20x-36x+84=30x-240-6x-84\)
\(\Leftrightarrow156-56x=24x-324\)
\(\Leftrightarrow-80x+480=0\Leftrightarrow x=-6\)
b, \(5\left(3x+5\right)-4\left(2x-3\right)=5x+3\left(2x-12\right)+1\)
\(\Leftrightarrow15x+25-8x+12=5x+6x-36+1\)
\(\Leftrightarrow7x+37=11x-35\)
\(\Leftrightarrow-4x+72=0\Leftrightarrow x=18\)
c, \(2\left(5x-8\right)-3\left(4x-5\right)=4\left(3x-4\right)+11\)
\(\Leftrightarrow10x-16-12x+15=12x-16+11\)
\(\Leftrightarrow-2x-1=12x-5\)
\(\Leftrightarrow-14x+4=0\Leftrightarrow x=\frac{2}{7}\)
d, \(5x-3\left\{4x-2\left[4x-3\left(5x-2\right)\right]\right\}=182\)
\(\Leftrightarrow5x-3\left[4x-15x+6\right]=182\)
\(\Leftrightarrow5x-3\left(-11x+6\right)=182\)
\(\Leftrightarrow5x+33x-18-182=0\)
\(\Leftrightarrow38x-200=0\Leftrightarrow x=\frac{100}{19}\)
(2x - 3)(2x + 2) - (4x - 2)(x - 5) = -16
<=> 4x2 + 4x - 6x + 6 - 4x2 - 20x - 2x = -16
<=> -24x = -16
<=> x = 2/3
tách hết ra